PENERAPAN MATERIAL FLOW COST ACCOUNTING (MFCA) UNTUK MENGUNGKAP BIAYA TERSEMBUNYI LIMBAH PADA UMKM KAFE : STUDI KASUS PADA KAFE DAN PASTRY DI KOTA MAKASSAR - Hairul Mar’i; Salsabila Arianto; Linda Arisanty Razak; Ismail Badollahi (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This study aims to reveal the hidden costs of material loss that have long been invisible in the conventional financial records of a café and pastry micro-enterprise (SME) in Makassar. The problem addressed is that small-scale cost accounting typically stops at cash-based profit and loss and records all material purchases as a single Cost of Goods Sold, leaving wasted materials unmeasured and unmanaged. Using a qualitative single-case-study approach, the research applies Material Flow Cost Accounting (MFCA) based on ISO 14051:2011 to trace material flows across four quantity centers and to allocate four cost elements—material, energy, system, and waste management—between product and non-product output. Because full physical weighing was not feasible, an estimative MFCA approach combined owner estimates with actual purchase prices from the financial records. The results show that total non-product output reached approximately IDR 2,350,850 per month, equivalent to 9.4% of total monthly operating cost, with an annual projection exceeding IDR 28 million that had never been recorded as a loss. The study concludes that sustainability accounting is affordable and feasible for SMEs using already-available data, and that MFCA information meaningfully supports efficiency decisions by the owner.